Guayaquil turístico. Lugares escasamente conocidos por la población local - Fabre Calle, John Arturo (2019)
The promotion of the tourist offer in Guayaquil has been increasing thanks to the joint or separate work of the municipal and state entities that have collaborated to increase the diffusion of recreation spaces. Although there are still little known centers of the city of Buenos Aires, which indicates that this system also has deficiencies. The realization of the present project has to do directly with the contribution to the tourist diffusion of the less known and less crowded places of the locality and its surroundings through a photo reportage that evidences the diverse and ample supply that exists in the city of Guayaquil.